A Study of Excursus on Śaivagamic Rituals in Śiva Temples as Practised at Present in South India and Sri Lanka - Balakailasanathasarma, M. (University of Jaffna, 2014)
This research paper which forms a continuation of The Study of excursus on Saivagamic Rituals in Siva temples of Agamic Saivism as practiced at present in South India and Sri Lanka, seeks to investigate another important aspect the rites and religious practice associated with temple worships. This investigation will reveal the fact that this new form of Siva worship did not by any means emerge suddenly, but that it was the outcome of a long and gradual development it is significant that such features of Puranic religion practices as agamic rituals aspects which were unknown to the vedic system of worship played an intrinsic rule in the later system of agamic worship. It is based directly on the Saivagamas which have carried out such elaboration to the utmost degree. For their rituals the priests in Saiva temples employ mantras taken from agamas which are assigned a high status among the religious text. The Saiva rituals are similarly performed from temple in South India and Sri Lanka. In this regard a special reference may be made to Purvakaranagama which contains agamic injunctions prescribing the employment of various vedic mantras. Similarly, many of the elements of vedic sacrifice can be shown to have become essential constituents of late Saiva ritualism. The Epic and Puranas must be regarded on essentially containing the statement of the Dravidian religion recorded in the Sanskrit language through the Saivagamic texts. The details of the rituals as outlined above vary from temple to temple. Most of the temples lacking in adequate funds cannot afford any claborate performance of rituals as far as the regular performance of the rituals even in their bare outline is concerned; only the big rich temples can properly afford it.
Keywords: Śaivagamic Rituals; Śaivaism; Sri Lanka